ENGLISH TEACHERS' BELIEFS ABOUT THE IMPLEMENTATION OF GENRE-BASED APPROACH IN TEACHING READING IN JUNIOR HIGH SCHOOL - Muhammad Rizqi Riyanto; Miftahul Furqon (Proceedings Series on Social Sciences & Humanities, 2026)
This study aims to investigate English teachers’ beliefs about the implementation of the Genre-Based Approach (GBA) in teaching reading at junior high schools. The research employed a qualitative design involving 18 English teachers from junior high schools in Karanglewas and Purwokerto Selatan districts, Banyumas Regency, Indonesia. Data were collected through a structured questionnaire and semi-structured interviews. The questionnaire was used to identify teachers’ familiarity with GBA and their initial beliefs about its implementation, while interviews with seven selected teachers provided deeper insights into their classroom practices, perceived benefits, and challenges. The data were analyzed using thematic analysis. The findings revealed that the teachers generally viewed GBA as a promising approach for teaching reading because it supports students in understanding text types, text structures, vocabulary, and reading comprehension. Teachers also believed that GBA could enhance students’ motivation, critical thinking, and ability to analyze texts. However, several challenges were identified, including limited instructional time, students’ diverse abilities, lack of motivation, limited resources, and insufficient teacher training. The study suggests that successful GBA implementation requires continuous professional development, adequate teaching materials, and collaborative support among teachers.